2016
DOI: 10.1371/journal.pone.0161738
|View full text |Cite
|
Sign up to set email alerts
|

Demand and Congestion in Multiplex Transportation Networks

Abstract: Urban transportation systems are multimodal, sociotechnical systems; however, while their multimodal aspect has received extensive attention in recent literature on multiplex networks, their sociotechnical aspect has been largely neglected. We present the first study of an urban transportation system using multiplex network analysis and validated Origin-Destination travel demand, with Riyadh’s planned metro as a case study. We develop methods for analyzing the impact of additional transportation layers on exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
2
30
0
1
Order By: Relevance
“…First, the actual topology of a transportation network is usually much more complicated than the topology of a simulated network. Second, the obtained coupling results usually deviate from real situations when using uniformly (randomly) generated travel demands [27]. Third, mobile phone data [30,31] cannot be used to capture the transfers between different network layers either.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…First, the actual topology of a transportation network is usually much more complicated than the topology of a simulated network. Second, the obtained coupling results usually deviate from real situations when using uniformly (randomly) generated travel demands [27]. Third, mobile phone data [30,31] cannot be used to capture the transfers between different network layers either.…”
Section: Introductionmentioning
confidence: 94%
“…An optimal operation speed is determined for London subway [24]. How operation speed of subway influences passenger travel time and road traffic congestion was studied using CDR (Call Details Records) data [27]. The results indicated that travel demand plays crucial quantitative and qualitative roles [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the emergence of congestion and delays requires, however, a step beyond the static structure of the network. First of all, in both private and public transportation the capacities of lines, roads and vehicles are of wide variety, and need to be taken into account to evaluate congestion and vulnerability [23,28,29]. Secondly, the transportation demand in cities is by no means homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]-and dynamic processes [9], such as mobility on urban multiplexes. The latter-which is the focus of this contribution, see next Section-has been tackled only recently [10][11][12].…”
Section: Introductionmentioning
confidence: 99%